Climate change impacts on irrigated agriculture in the Guadiana riverbasin (Portugal) - Valverde, Pedro (2015)
This study evaluates climate change potential impacts on irrigated agriculture in the Guadiana river basin, in the south of Portugal, by running long-term soil water balance simulations using the ISAREG model and taking into consideration the maximum potential yield. The ISAREG simulations were focused in aset of the most locally representative crops to assess the evolution of net and total water requirements, considering a monthly time step for two 30-year future periods, (2011–2040) and (2041–2070). Reference evapotranspiration was estimated using the temperature-based Hargreaves–Samani equation, and the simulations were performed using, as inputs, a combination of five climate change scenarios built using the Ensemble-Delta technique from CMIP3 climate projections datasets to set different alternative climate change bracketing conditions for rainfall and air temperature. Water balance outputs for different climate scenarios were combined with four agricultural scenarios allowing for the estimation of total irrigation requirements. A general increase in crop irrigation requirements was estimated, mainly for those crops as maize, pasture, and orchards that are already big irrigation water consumers. Crops as olive groves and vineyards, well adapted to the Mediterranean conditions, show less sensitivity to climate change. The combined results of crop irrigation requirements for climate change and agricultural scenarios allow for the expectation of sustainability for the agricultural scenarios A and C, essentially defined by the complete use of the irrigation network and systems currently being constructed with the Alqueva project, but not for the ambitious irrigation area expanding scenario B.